P-03 Development of a hospice education collaborative across Sussex. (19th November 2022) - Evans, Helen; Burden, Rebecca; Moorey, Alison; Barclay, David; Coton, Rachel
Abstract : Background: The seven Sussex hospices have begun to develop a unique education collaborative focusing on external education delivery (this is one strand of collaboration). The benefits include: Pooling of resources, knowledge and capacity. Improved sustainability. Joint funding bids. Robust evaluations (Bryan, Berg, Reed, et al., 2016. BMJ Support Palliat Care. 6: 91) Extend collective reach. Reduce inequality in education access. Workforce development. An interdisciplinary approach and framework will, also, yield advancement in palliative and end of life care (MacLeod Dyes, Prestia, Levene, et al., 2020. J Holist Nurs. 38: 320) and extend collective reach. Whilst there is a small amount of literature there is an appetite for this as seen by a wider collaboration on vocational education by Hospice UK (Garbett, 2016, BMJ Support Palliat Care. 6:94). Other collaborations are either smaller (Pilgrims Hospices, 2021) or specific projects (Vandeweghe, Heaps, Glynne-Owen, et al., 2021, BMJ Support Palliat Care. 11:68). Some recent partnerships were formed to meet the educational demands due to the pandemic (Pilgrims Hospices, 2021). Aim: To develop a Sussex-wide hospice education collaborative by April 2023. Methods: This project is being developed alongside the emergence of the new NHS Integrated Care Board. Post the appointment of a Project Manager at the end of 2021 after an initial period of ground work a business plan is reaching fruition. The collaboration will include the Sussex Project ECHO team. This is set alongside a conclusion from the seven Chief Executive Officers on the delivery vehicle for this separate entity. An initial steering group meeting with key representatives was held in April 2022. Working groups to support the steering group mission will commence shortly. Key commissioners in Sussex are engaged in the project. Results: Work in progress. Conclusion: Work in progress. Whilst other models exist in palliative and end of life care they do not represent the same scale and structure in development in Sussex. The dual issues of economics and lack of skilled staff highlight the need for a more efficient use of resources. The creation of a separate entity to house this collaborative is unique.